Health and safety critical control management : good practice guide. (International Council on Mining and Metals, 2015)
ICMM has published practical guidance on preventing the most serious types of health and safety incidents in mining and metals. The approach described in this book is designed to identify and manage acts, objects or systems onsite - the "critical controls" - that need to be in place to either prevent a serious incident occurring or minimize the consequences if a serious incident were to occur.